(untitled) (Sirte University Journal of Humanities, 2025)
This study aims to examine the impact of diversifying income sources on the profitability of the Libyan banking system for the period 2005-2020, specifically before and after Law No. (1) of 2013, which prohibits usurious transactions. This study provides an academic contribution to the banking sector and scientific research by identifying the impact of this law on the profitability of the Libyan banking system. The study data were analyzed using ordinary least squares (OLS) regression model, and the model was estimated using the econometric software Stata 15. The study showed that there is a statistically significant relationship between income diversification and the profitability of the Libyan banking system before and after Law No. (1) of 2013. Our results indicate that increased income diversification before and after Law No. (1) leads to increased profitability of the Libyan banking system. Moreover, this increase was larger and more pronounced before this law than after the issuance of Law No. (1). The reason may be banks relied on a wider range of income sources , such as loans for economic activities, real estate loans for production, services, and industry, and social loans, whereas after Law No. (1) of 2013, banks focused only on Islamic Murabaha only. This study reached several recommendations, the most important of which is that the Libyan banking system can improve profitability by increasing the diversity of income sources.